Exploring English for Specific Purpose Students' Perceptions of Digital Materials in English Language Learning: Benefits, Challenges, and Recommendations - Romadhon, Romadhon (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2023)
This study aimed to discover how English for Specific Purposes (ESP) students perceived the utilization of digital resources during their language-learning process. A questionnaire with 20 statements divided into categories like usability, engagement, problems, and recommendations was completed by 28 study participants. According to a Likert scale that ranged from highly agree to strongly disagree, the participants gave their answers. The research found that ESP students generally had favourable opinions of digital resources. They thought the resources were easy to use, available on a variety of platforms and devices, and offered flexibility in their study. The participants acknowledged the motivating qualities of digital resources as well as their role in motivation and the growth of English language proficiency. They did, nonetheless, draw attention to several difficulties, such as the need for more help and technical problems. These opinions of ESP students toward digital materials are revealed, and this knowledge aids teachers and curriculum writers in creating resources for language acquisition that are beneficial. Future studies can concentrate on resolving the issues found and improving the advantages of digital resources in ESP scenarios.